Analisis Faktor-Faktor yang Mempengaruhi Biaya Transaksi Nasabah pada PT Bank Perkreditan Rakyat Nusuma Gondang Legi Malang - Anggitaningsih , Retna (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This study aims to analyze the factors that affect customer transaction costs at PT Bank Perkreditan Rakyat Nusuma Gondang Legi, Malang, using qualitative methods through library research using secondary data from sources such as the bank's official website, books, journals, and related articles. The results show that the cost of obtaining third-party funds has a significant positive effect on transaction costs, while bank operational costs do not. Target profit margin and timely payment incentive costs have a significant positive effect, but loan risk costs and asset depreciation are not significant. In conclusion, factors related to bank management and operations, including cost of obtaining funds, operational costs, target profit margin, timely payment incentive costs, and asset depreciation costs, have a significant effect on customer transaction costs. Effective management is needed to minimize transaction costs and improve the efficiency of the banking industry, providing additional insights for further analysis development in supporting the growth of the banking sector